Promoting High Quality Work: Obstacles and Opportunities - Spencer, David A. (2013)
This article addresses competing arguments from ethics as well as economics about the obstacles and opportunities for promoting high quality work (i.e. work that sustains and enhances well-being). It ultimately defends on ethical as well as economic grounds the case for maximising the number and equalising the distribution of high quality work opportunities and outlines some policy measures that might be used to achieve the latter objective. The article contributes to the business ethics literature principally by offering a systematic and interdisciplinary analysis of the scope and necessity for progress in the quality of working life.
Keywords: Policies for high quality work; Efficiency; High quality work; Well-being at work; Work quality